Comparison of Laser Doppler and Laser-Assisted Indocyanine Green Angiography Prediction of Flap Survival in a Novel Modification of the McFarlane Flap. Issue 1 (July 2015) - Fourman, Mitchell Stephen; Gersch, Robert P.; Phillips, Brett T.; Nasser, Ahmed; Rivara, Andrew; Verma, Richa; Dagum, Alexander B.; Rosengart, Todd K.; Bui, Duc T.
Abstract : Background: The McFarlane rat ischemic dorsal skin flap model has been commonly used for clinical vector studies, as well as the testing of noninvasive diagnostics. However, variability of this model secondary to flap contact with the wound bed has led many to question its validity. Here we present a novel modification to the McFarlane skin flap using sterile silicone. We also use this model to test the prognostic efficacy of laser-assisted indocyanine green (ICG) angiography and laser Doppler imaging (LDI). Methodology: A 3 × 9-cm dorsal skin flap with a cranially based pedicle was created, centered 1 cm distal to the scapulae. The flap was undermined, and in one of the 2 groups, a sterile silicone sheet was placed onto the wound bed. All flaps were then reapproximated with sutures 1-cm intervals. Clinical assessment and perfusion imaging was performed immediately postoperative, and at 24, 48, and 72 hours postsurgery. Postoperative day 7 clinical assessment was obtained before euthanasia. Results: A comparative study using silicone blocked versus unblocked models (n = 6 per group) showed that, clinically, both models had equivalent flap survival [8.5 (0.913) vs 9.5 (1.01) cm 2 ]. However, a statistically significant increase in perfusion in the mid-third of unblocked models was observed on POD3 [20.28% (2.7%) vs blocked 13.45% (2.5%), P < 0.05], with a similar increase in the distal third on POD7 [18.73% (2.064%) vs 10.91% (4.19%), P < 0.05]. A prognostic study comparing LDI and ICG angiography prediction of POD7 survival at early time points (n = 10) found that LDI underpredicted flap survival at early time points [84.2% (12.03%) on POD0, 87.35% (16.11%) on POD1]. In contrast, ICG was more proficient [100.1% (10.1%) on POD0]. Conclusions: We present a modification of the McFarlane skin flap model that results in similar clinical results, but with a noted reduction in perfusion inconsistencies noted in unblocked models. The ICG angiography is superior to LDI in predicting POD7 flap necrosis within the first 48 hours postinjury. Future work will focus on histologic validation of our model, and vector efficacy testing.